Pengaruh Inovasi Produk Dan Kualitas Produk Terhadap Kepuasan Konsumen Dengan Keputusan Pembelian Sebagai Pemediasi (Studi Kasus Pada Produk Skincare MS GLOW) - Jati, Virginus Mario; Nuvriasari, Audita (Universitas Islam Kadiri, 2024)
Abstract The development of the beauty business today is growing rapidly in line with changes in people's lifestyles which pay more attention to appearance. Good quality beauty products can influence purchasing decisions. This research aims to see how product innovation and product quality influence consumer satisfaction with purchasing decisions for MS Glow skincare products. The type of research used is quantitative research. The population in this study were users of Ms Glow Skincare products who live in Yogyakarta. The sampling technique used in this research was purposive sampling with a sample size of 100 people. The research results show (1) Product innovation has a positive effect on MS Glow Skincare consumer satisfaction. (2) Product quality has a positive and significant effect on consumer satisfaction. (3) Product innovation has a positive and significant effect on consumer purchasing decisions. (4) Product quality has a positive and significant effect on consumer purchasing decisions. (5) Purchasing decisions have a positive and significant effect on consumer satisfaction. (6) Purchasing decisions significantly mediate product innovation on Ms Glow consumer satisfaction in Yogyakarta. (7) Purchasing decisions significantly mediate product quality on Ms Glow consumer satisfaction in Yogyakarta.